Toward a New Gold Standard for Early Safety: Automated Temperature-Controlled hERG Test on the PatchLiner® - Polonchuk, Liudmila (Frontiers in Pharmacology, 2012)
In the present study, the Patchliner® temperature-controlled automated patch clamp system was evaluated for testing actions of drugs on K+ currents through hERG channels expressed in CHO cells at 35-37°C. Obtained IC50 values for a set of reference drugs were matched with those obtained using conventional voltage clamp technique. Comparison of the results demonstrated good correlation between the data obtained by means of conventional and automated electrophysiology. Based on these results, Patchliner® offers innovative automated electrophysiology platform for conducting the hERG assay with substantial throughput increase and advantage of physiological temperature. The Patchliner® -based automated patch clamp system with temperature control allows a fast, accurate direct assessment of channel function in a short timeframe and sets a new standard to study ion channels and identify potential proarrhythmic side effects in drug safety testing.